A major practicum report for Motherland Food Products, Balongis, Barangay Balulang, Cagayan de Oro City - Pajarito, Queenzyl Delbo (2006)
The plant practice was conducted as a part of the curriculum for the Bachelor of Science in Food Technology. The student was exposed to the actual operation of food industry, specifically at the MFP Company, specifically its fruit puree production. The 288 hours of plant practice provided the student trainee with exposure to the plant?s production lines. All areas of operations of the company such s receiving of raw materials, processing up to the delivery of some of the products were observed and data structure, history, and product profile were then documented in this manuscript wherein the theories and principles learned academically and the learning experience in the real world of food industry are put together using a systematized unbiased technical analysis. Insights and recommendations were also given after the analysis